2009
DOI: 10.2146/ajhp080552
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation at an academic medical center: Implementation of a comprehensive program from admission to discharge

Abstract: A pharmacy-driven multidisciplinary admission history and medication reconciliation process has reduced medication errors in an academic medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 7 publications
2
81
0
3
Order By: Relevance
“…Medical reconciliation requires collaboration between healthcare providers, nurses and pharmacists. In various studies, pharmacist involvement in medication reconciliation showed decreased medication errors and improved patient outcome [12,13]. Another study revealed nurse-pharmacy communication can significantly reduce medication errors [14].…”
Section: Discussionmentioning
confidence: 99%
“…Medical reconciliation requires collaboration between healthcare providers, nurses and pharmacists. In various studies, pharmacist involvement in medication reconciliation showed decreased medication errors and improved patient outcome [12,13]. Another study revealed nurse-pharmacy communication can significantly reduce medication errors [14].…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 The need to maintain and communicate accurate patient medication information via medication reconciliation is included in The Joint Commission National Patient Safety Goals 2014. 16 This helps ensure that future medications are prescribed safely, such as new orders for the FTS.…”
Section: Figure 3 Percentage Of Inpatient Fentanyl Transdermal Systementioning
confidence: 99%
“…[9,10,11,12], az eltérő ellátórendszerekbe [9,10,11,12,13] és különböző profi lú osztályok gyakorlatába átültethető módszer [9,10,11,12]. A gyakorlat megvalósítását a betegbiztonság javítását célzó kampányokban aktív szerepet vállaló szervezetek is támogatják.…”
Section: Táblázatunclassified